(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Psychotic disorders, including schizophrenia, significantly impact individuals’ mental health, necessitating innovative therapeutic approaches. This study evaluates the antipsychotic potential of ethanolic extracts of Mentha arvensis L. leaves through apomorphine-induced psychosis in rats. The extract’s phytochemical profile revealed the presence of alkaloids, flavonoids, and phenols, among others, indicating its bioactive potential. In vitro antioxidant assays demonstrated notable nitric oxide and superoxide anion scavenging activities, suggesting its neuroprotective properties. Behavioral studies, including the pole climbing and catatonic tests, highlighted significant improvements in motor coordination and reduced catatonic symptoms with the extract, especially at 200 mg/kg. Biochemical analyses indicated a restorative effect on dopamine levels and modulation of monoamine oxidase (MAO-A and MAO-B) activities, reflecting its potential mechanisms of antipsychotic action. These findings align with traditional medicinal uses of Mentha arvensis for mental health. The results underscore the therapeutic promise of Mentha arvensis in managing psychosis, with implications for its use as a natural adjunctive treatment. Further research is needed to isolate active compounds, understand molecular mechanisms, and assess safety and efficacy in clinical settings. This study highlights the integration of phytochemical and pharmacological approaches to uncover novel antipsychotic agents.